The Social Worlds of Ancient Jews and Christians : Essays in Honor of L. Michael White - Boin, Douglas,; Gunderson, Jaimie,; Keddie, Anthony, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
This volume contains fifteen essays in honor of L. Michael White, whose work has been influential in exploring the social histories of ancient Jews and Christians within the Graeco-Roman world. Following an introduction that highlights some of White's main scholarly contributions, the essays are grouped into three topic areas: Paul and his Legacy, Social Relations, and Material Culture. The essays are united by an interest in reconstructing the social worlds of ancient Jews and Christians through careful analysis of literary sources and material culture in their most precise ancient contexts.